The Influence of Financial Performance and Company Size on Zakat Payments of PT. Bank Muamalat Indonesia Tbk - Anisah, Rahmi; Rohim, Ade Nur (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
The development of total assets of Islamic Commercial Banks (BUS) continues to increase every year. In addition, the potential for zakat in Indonesia is also increasing every year, including from the corporate zakat sector. However, the increase is not in line with the realization of national zakat collection. In fact, corporate zakat has the highest contribution compared to other types of zakat, especially in terms of zakat potential. An in-depth analysis of the factors that influence corporate zakat payment is needed. This study aims to analyze several factors that affect corporate zakat such as ROA, CAR, FDR, NPF and Company Size. The research was conducted at PT Bank Muamalat Indonesia Tbk using secondary data. This research data was analyzed by multiple linear regression. The research sample used data published in the financial statements of PT Bank Muamalat Indonesia Tbk in 2012 - 2022. The results of this study state that the variables ROA, CAR, FDR, NPF and Company Size together have an effect on corporate zakat. As well as, partially states that the ROA variable affects the company's zakat, while the CAR, FDR, NPF and Company Size variables have no effect on corporate zakat. The results of this study are expected to contribute to the level of literacy and realization of corporate zakat collection, especially from the BUS sector.